2021
DOI: 10.1007/s11356-021-14612-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and dynamics of environmental awareness, sustainable consumption and social responsibility in Malaysia

Abstract: Despite a profound evidence of the human unsustainable behaviours’ impact on the environment, stark disparities prevail on this narrative especially in the context of the current epidemiological situation ushered by the COVID-19. The ongoing pandemic is a global public health concern due to its sagacious impacts on environmental sustainability, social responsibility and people’s quality of life. This study primarily focuses on analysing the impact of COVID-19 (COV) on the environmental awareness (EA), sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 127 publications
(132 reference statements)
5
24
0
2
Order By: Relevance
“…In addition, in this same previous study, we observed an increase in ethical concern (21% of the participants) and natural content (19%) as food choice motives during the lockdown, which suggests a growing awareness of the importance of the environmental impact of food choices (10). These results echoed the raise in environmental awareness during the COVID-19 outbreak that has been documented and described by numerous scientists (11)(12)(13)(14)(15). However, to our knowledge, the impact of the COVID-19 outbreak on the environmental impact of diets has never been studied.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, in this same previous study, we observed an increase in ethical concern (21% of the participants) and natural content (19%) as food choice motives during the lockdown, which suggests a growing awareness of the importance of the environmental impact of food choices (10). These results echoed the raise in environmental awareness during the COVID-19 outbreak that has been documented and described by numerous scientists (11)(12)(13)(14)(15). However, to our knowledge, the impact of the COVID-19 outbreak on the environmental impact of diets has never been studied.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, it has been found that COVID-19 changes the perception of green consumption, organic food, and food safety among Malaysians ( Safuan et al, 2021 ). Furthermore, in the context of COVID-19 pandemic, a focus on eating healthier diet and environmental awareness has been prominent and individuals were worried about the environment and its effect on their health ( Naja and Hamadeh, 2020 ; Ali Q. et al, 2021 ). Evidently, the coronavirus pandemic has affected individual’s feelings and thoughts, hygiene practices, and consumption patterns.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, in Canada, Ikiz et al (2021) studied the changes on recycling habits in multi-residential buildings in Toronto and found out that during the early stages of the con nement, due to the halt of recycling activities, waste separation practices decreased to a large extent. However, the pandemic conditions also motivated a greater environmental awareness (Ali et al, 2021). Other authors have found positive changes in waste management practices and environmental awareness during the pandemic.…”
Section: Resultsmentioning
confidence: 99%